"A GRIM MEMORIAL OF ITS THOROUGH WORK OF DEVASTATION AND DESOLATION": RACE AND MEMORY IN THE AFTERMATH OF THE 1893 SEA ISLAND STORM. (27th April 2018) - Bland, Robert D.
Abstract : "'A Grim Memorial of Its Thorough Work of Devastation and Desolation': Race and Memory in the Aftermath of the 1893 Sea Island Storm" explores the political struggle that ensued in the aftermath of the August 1893 hurricane. The storm, which decimated the predominantly African American South Carolina Sea Islands, required a nine-month relief effort to assist the region's citizens in their time of need. Led by the American Red Cross, the relief effort became a new proxy for a long-standing debate over the legacy of Reconstruction and the meaning of black citizenship. This battle, waged by leaders in South Carolina's Democratic Party, Red Cross officials, writers in the national press, former abolitionists, and African Americans living in the South Carolina Sea Islands, exposed growing fissures in how Americans understood notions of charity and self-help. More than a battleground for still-nascent ideas of disaster relief, the political turmoil that followed the 1893 Sea Island Storm played a critical role in redefining the racial boundaries of the United States on the eve of the Jim Crow era.